Pemanfaatan daun Indigofera zollingeriana sebagai bahan pakan ikan patin (Pangasius sp.) - Retno Cahya Mukti; Danang Yonarta; Aldila Din Pangawikan (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2019)
Abstract. The feed is one of the components that support the growth and survival in fish culture. One of the alternative feed ingredients which could use as other feed ingredient was Indigofera zollingeriana leaves. The aims of this research was to determine the use of Indigofera zollingeriana leaves on the growth performance of Patin (Pangasius sp.). This research consisted of five treatments and three replications. Indigofera zollingeriana leaves were used in the diet amount of P0 (0%) (without Indigofera zollingeriana leaves addition ), P1 (10% Indigofera zollingeriana leaves addition), P2 (20% Indigofera zollingeriana leaves addition), P3 (30% Indigofera zollingeriana leaves addition), and P4 (40% Indigofera zollingeriana leaves addition). The result showed that the use of Indigofera zollingeriana leaves had a significant effect on the fish growth performance. The use of 20% zollingeriana Indigofera produced the best results of the absolute weight of 2.15 g, 1.00% daily growth rate and feed efficiency of 44.60%.Keywords: Patin, feed ingredient, Indigofera zollingeriana leaveAbstrak. Pakan merupakan komponen yang menunjang pertumbuhan dan kelangsungan hidup dalam budidaya ikan. Salah satu bahan baku alternatif yang dapat digunakan sebagai bahan pakan ikan yaitu daun Indigofera zollingeriana. Penelitian ini bertujuan untuk mengetahui pengaruh penggunaan daun Indigofera zollingeriana terhadap kinerja pertumbuhan pada ikan patin. Penelitian ini terdiri dari lima perlakuan dan tiga ulangan. Perlakuan penggunaan daun Indigofera zollingeriana terdiri dari P0(0%) (tanpa penambahan daun Indigofera zollingeriana), P1 (penambahan daun Indigofera zollingeriana 10%), P2 (penambahan daun Indigofera zollingeriana 20%), P3 (penambahan daun Indigofera zollingeriana 30%), dan P4 (penambahan daun Indigofera zollingeriana 40%). Hasil penelitian menunjukkan bahwa penambahan daun Indigofera zollingeriana menunjukkan kinerja pertumbuhan pada ikan patin. Penambahan Indigofera zollingeriana sebanyak 20% menghasilkan hasil terbaik yaitu pertumbuhan bobot mutlak sebesar 2,15 g, laju pertumbuhan harian 1,00% serta efisiensi pakan sebesar 44,60%.Kata Kunci: Bahan pakan, daun Indigofera zollingeriana, ikan patin